Thrixspermum patkaiensis sp. nov. (Vandeae: Aeridinae) from Assam, northeast India - Gogoi, Khyanjeet (Universidad de Costa Rica, 2022)
A new species of orchid, Thrixspermum patkaiensis from the tropical evergreen forest in Dehing Patkai National Park, Assam, India, is described. It is morphologically similar to T. musciflorum and T. formosanum but distinct from these species by the inflorescence 12–18 cm long; the lip with purplish bands and glandular hairy both side of the side lobes and the epichile forming a rim of glandular hairs.